2019
DOI: 10.1021/acs.est.9b00967
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic Insight into the Uptake and Fate of Persistent Organic Pollutants in Sea Ice

Abstract: The fate of persistent organic pollutants in sea ice is a poorly researched area and yet ice serves as an important habitat for organisms at the base of the marine foodweb. This study presents laboratory-controlled experiments to investigate the mechanisms governing the fate of organic contaminants in sea ice grown from artificial seawater. Sea ice formation was shown to result in the entrainment of chemicals from seawater, and concentration profiles in bulk ice generally showed the highest levels in both the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
39
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

4
4

Authors

Journals

citations
Cited by 23 publications
(40 citation statements)
references
References 27 publications
1
39
0
Order By: Relevance
“…These findings are also supported by previous studies in sea ice which display similar findings for hydrophobic POPs of varying molecular mass and aqueous solubility. 13 Partitioning of PFAS to ice surfaces can be linked to hydrophobic interactions, which increase with carbon chain length. Interestingly, differences were also observed between PFAS with the same carbon chain length (e.g., 6:2 FTSA, PFOS, and PFOA) which shows that other physicochemical properties also control the their behavior in sea ice, such as the number of fluorine atoms and different functional groups.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings are also supported by previous studies in sea ice which display similar findings for hydrophobic POPs of varying molecular mass and aqueous solubility. 13 Partitioning of PFAS to ice surfaces can be linked to hydrophobic interactions, which increase with carbon chain length. Interestingly, differences were also observed between PFAS with the same carbon chain length (e.g., 6:2 FTSA, PFOS, and PFOA) which shows that other physicochemical properties also control the their behavior in sea ice, such as the number of fluorine atoms and different functional groups.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, experimental studies in artificial sea ice also showed elevated levels of organic pollutants in brine and demonstrated their distribution in newly formed bulk sea ice was primarily due to the movement of brine. 13 Furthermore, α-HCH was released at a faster rate from melting sea ice compared to less soluble chemicals (i.e., BDE-47, BDE-99), suggesting that partitioning of chemicals between internal solid ice surfaces and liquid brine was also an important process. Due to their known surface acting properties, we anticipate PFAS to display partitioning within sea ice which could result in their enrichment, presenting a motivation to undertake similar experiments to investigate their behavior during sea ice formation and subsequent melt.…”
Section: Introductionmentioning
confidence: 99%
“…Elevated concentrations of PFAAs in the uppermost ice layers of sea ice may be a result of entrainment of chemicals present in seawater during initial sea ice formation. 15 , 43 However, snow is also likely to play an important role in the delivery of PFAAs 44 to sea ice with the amount and timing of snowfall deposition likely to affect accumulation dynamics.…”
Section: Resultsmentioning
confidence: 99%
“… 10 , 15 Sea ice brine has also been shown to contain contaminant concentrations at levels significantly greater than those observed in the underlying seawater. 10 , 15 In the warming Arctic Ocean dominated by brine-rich single-season ice, this has important implications for contaminant exposure to the many organisms situated at the base of the pelagic food web, which are abundant in sea ice. Sympagic organisms, such as ice algae and associated heterotrophic protists and metazoans, inhabit a network of brine inclusions and brine channels at the base of the ice and may be particularly vulnerable to brine which is enriched in contaminants.…”
Section: Introductionmentioning
confidence: 99%
“…We grew free-floating sea ice to (11.0 ± 0.9) cm (run 1) and (16.4 ± 2.7) cm (run 2) thickness (mean and standard deviation of measured ice core thickness). Measurements of sea-ice temperature, thickness, and the initial ocean salinity were used to force the model, which has been used previously to model experiments in the RvG-ASIC (Garnett et al, 2019;Thomas et al, 2020). We used the Griewank and Notz (2013) https://doi.org/10.5194/amt-2020-392 Preprint.…”
mentioning
confidence: 99%